Regulatory T cells and vaccine effectiveness in older adults. Challenges and prospects - Batista-Duharte, Alexander [UNESP]; Pera, Alejandra; Aliño, Salvador F.; Solana, Rafael (Elsevier, 2021)
Since the discovery of lymphocytes with immunosuppressive activity, increasing interest has arisen in their possible influence on the immune response induced by vaccines. Regulatory T cells (Tregs) are essential for maintaining peripheral tolerance, preventing autoimmune diseases, and limiting chronic inflammatory diseases. However, they also limit beneficial immune responses by suppressing anti-infectious and anti-tumor immunity. Mounting evidence suggests that Tregs are involved, at least in part, in the low effectiveness of immunization against various diseases where it has been difficult to obtain protective vaccines. Interestingly, increased activity of Tregs is associated with aging, suggesting a key role for these cells in the lower vaccine effectiveness observed in older people. In this review, we analyze the impact of Tregs on vaccination, with a focus on older adults. Finally, we address an overview of current strategies for Tregs modulation with potential application to improve the effectiveness of future vaccines targeting older populations.
Keywords: Adjuvants; Immune response; Immunosenescense; Older adults; Regulatory T cells; SARS-CoV-2; Vaccine